Two novel transporters NtNRAMP6a and NtNRAMP6b are involved in cadmium transport in tobacco (Nicotiana tabacum L.) - Zhang, Jishun (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.